Expert-Augmented Computational Drug Repurposing Identified Baricitinib as a Treatment for COVID-19 - Smith, Daniel P.; Oechsle, Olly; Rawling, Michael J.; Savory, Ed; Lacoste, Alix M.B.; Richardson, Peter John (Frontiers in Pharmacology, 2021)
The onset of the 2019 Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic necessitated the identification of approved drugs which could be used to treat the disease, before the development, approval and widespread administration of suitable vaccines. To identify such a drug, we used a visual analytics workflow where computational tools applied over an AI-enhanced biomedical knowledge graph were combined with human expertise. The workflow comprised rapid augmentation of knowledge graph information from recent literature using machine learning (ML) based extraction, with human-guided iterative queries of the graph. Using this workflow, we identified the rheumatoid arthritis drug baricitinib as both an antiviral and anti-inflammatory therapy. The effectiveness of baricitinib was substantiated by the recent publication of the data from the ACTT-2 randomised Phase 3 trial, followed by emergency approval for use by the FDA, and a report from the CoV-BARRIER trial confirming significant reductions in mortality with baricitinib compared to standard of care. Such methods, that iteratively combine computational tools with human expertise hold promise beyond drug repurposing, particularly in areas of biological research where relevant data may be lacking or hidden in the mass of available biomedical data.